PENDAMPINGAN PROGRAM PEMASARAN PRODUK UMKM PADA KELOMPOK TANI KECAMATAN ENGGANO - Khopangsang, Arbit; Eka sri Wahyuni; Yenti Sumarni (Universitas Muhammadiyah Bengkulu, 2025)
The purpose of the UMKM product marketing program is to educate members of the Aksa Tani farmer group to improve their understanding and knowledge in understanding the marketing of UMKM products in the Aksa Tani farmer group in Kaana village, Enggano sub-district, North Bengkulu district, Bengkulu province. Before the implementation, many members of the farmer group still did not understand the marketing of UMKM products. This study is a qualitative study that explores the product marketing model in the UMKM Farmer Group in Enggano District.